Stepwise acquisition of unique epigenetic signatures during differentiation of tissue Treg cells - Braband, Kathrin L.; Kaufmann, Tamara; Floess, Stefan; Zou, Mangge; Huehn, Jochen; Delacher, Michael (Frontiers in Immunology, 2022)
Regulatory T cells in non-lymphoid tissues are not only critical for maintaining self-tolerance, but are also important for promoting organ homeostasis and tissue repair. It is proposed that the generation of tissue Treg cells is a stepwise, multi-site process, accompanied by extensive epigenome remodeling, finally leading to the acquisition of unique tissue-specific epigenetic signatures. This process is initiated in the thymus, where Treg cells acquire core phenotypic and functional properties, followed by a priming step in secondary lymphoid organs that permits Treg cells to exit the lymphoid organs and seed into non-lymphoid tissues. There, a final specialization process takes place in response to unique microenvironmental cues in the respective tissue. In this review, we will summarize recent findings on this multi-site tissue Treg cell differentiation and highlight the importance of epigenetic remodeling during these stepwise events.